Mechanism of stress transmission and feasibility of mining the lower coal seam under repeated mining in close-multiple coal seams - Yang, Dapeng; Li, Tiezheng; Li, Yang; Ren, Yuqi (Frontiers in Earth Science, 2024)
Mining in an upper coal seam results in the redistribution of vertical stress within a lower coal seam until a new equilibrium state is attained. Close-multiple coal seams mining faces the occurrence of multi-goafs and a complex stress environment. Based on a case study of close-multiple coal seams with repeated mining in the Qianjiaying coal mine, a stress distribution model of the floor in the coal seam striking range was established by optimizing the load form of the abutment pressure. The floor stress state after primary and repeated mining of upper coal seams was analyzed in a visual and quantitative manner. The concentrations of vertical stress, horizontal stress, and shear stress are all located in the floor under the coal rib after primary and repeated mining. The curve of stresses gradually levels off as the depth of the floor increases, indicating a diminishing influence of mining-induced stress from the upper coal seam. Based on the stress analysis by numerical simulations, the overall lower coal seam remains in a state of large-scale stress relief. Stress relief occurred twice under repeated mining, which indicates that the lower coal seam has favorable mining feasibility. The results of the study can provide scientific guidance to prevent mining accidents.